Realiti Perpaduan Ummah dan Cabarannya: Analisis Dari Perspektif Pemikiran Islam - Kamaruddin bin W.Ali; Madya Madya (Lembaga penelitian dan pengabdian kepada masyrakat, 2010)
Ummah has various connotations which depend on perspectives from various sources. In Islam, ummah has certain element and criteria and especially if related to Islam as “a way of life”. Currently, ummah is facing tough challenges from within and outside. Challenge from within is represented by many perspectives, as well as from outside. Both challenges could not be easily wiped away and at certain level, can damage the ummah if they are not handled carefully. Obviously, challenge from outside is clearer than from within. To know the challenges fundamentally can easily help to find the fair solution. It is indeed a must to differentiate the secondary challenge that is produced by fundamental challenge. Historical perspective could also be examined to see the change that happened from the earlier stage until now in order to observe the solidarity of the ummah themselves throughout the stages. The strength and weakness from fundamental aspect can determine the identity and survival of the ummah in the globalised world. This paper, as it is presented here tries to see, to elaborate and to observe the strength and weakness of ummah fundamentally and its relation to the survival of ummah themselves.